A Dynamical Study of Risk Factors in Intracerebral Hemorrhage using Multivariate Approach - Siddiqui, Afaq Ahmed; Siddiqui, Junaid S.; Wasay, Mohammad; Azam, S. Iqbal; Ahmed, Asif (International Journal of Statistics in Medical Research, 2013)
The purpose of this study is to investigate the effects of clinical covariates to the outcome of Intracerebral Hemorrhage (ICH) patients in terms of best fitted and excellent discriminate model of binary response variable. Clinical data of 985 patients with ICH have collected using the International classification of diseases, Ninth revision codes. The diagnosis of ICH was confirmed by neuro-imaging in all patients. Univariate analysis revealed that out of 88 covariates 46 were found to be significant (p<0.05). The multivariable analysis using multiple logistic regressions, exhibited a significant negative relationship between ICH and hypertension. The improvement among ICH patients having hypertension was 0.5 (p=0.001, ARR=0.5, 95% C.I. 0.3 – 0.8). The improvement among ICH patients using antihypertensive medicine was 1.3 (p = 0.016, ARR=1.3, 95% C.I. 1.1 – 1.5). Thus present study showed that ICH has strong relationship with use of antihypertensive medicine. The improvement of patients who were using antihypertensive medicine at the time of discharge was 3.0 times (p < 0.0001, ARR=3.0, 95% C.I. 2.7 – 3.2) as compared to those who did not use antihypertensive medicine. The change in ARR from 1.3 to 3.0 times shows that the use of antihypertensive medicine and ICH outcome variable are positively associated. The change in ARR of hypertensive range of SBP also indicates that the blood pressure range and ICH outcome variable are negatively associated. The neurological symptomatology, slurred speech and double vision are important factors of proposed statistical models. Moreover, a clear decrease was found in mental status from normal to coma in applicable model. Surgery is an important part of recovery, and estimated that the improvement among the ICH patients, who were treated with surgery, was 1.4 times with significant p-value in best fitted models. The complication of pneumonia during treatment of ICH subjects has highly significant negative association with outcome variable. Present Model has 0.892 area under the curve with sensitivity (0.852), specificity (0.793) and p-value (0.204). This indicates that the model gives the impression to fit quite well for predictive performance of the ICH outcome variable and the model is excellent model.